Fruit Vendor, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Ace Studio, Trinidad; Printed in Scotland by Robert MacLehose and Co. Ltd., 2009)
A vendor selling fruit from a vending stand. Postcard number 11.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Trinidad and Tobago; Street vendors--Trinidad and Tobago; Vending stands--Trinidad and Tobago; Fruit--Trinidad and Tobago; Hats--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago